Eucalyptus plantation reduces diversity and disrupts predator-prey correlations of soil invertebrates within Atlantic Forest - Martello, Felipe [UNESP]; Dáttilo, Wesley; Souza-Campana, Débora Rodrigues; Medeiros, Hugo Reis [UNESP]; Silva, Rogério R.; Ribeiro, Milton Cezar [UNESP]; Morini, Maria Santina C. (Elsevier, 2024)
Human activities in the Anthropocene have led to the conversion of a significant area of the Earth's surface to agroecosystems, including tree plantations such as eucalyptus. Brazil, as the largest producer of eucalyptus timber, faces the challenge of preserving its rich biodiversity, particularly in the Atlantic Forest biome, which is one of the world's most threatened and diverse. This study aimed to assess the impact of eucalyptus plantation on soil invertebrate communities compared to that of native forest remnants. We sampled ants, beetles, springtails, and spiders as model groups to evaluate the alpha diversity and composition of soil invertebrates in these forests. We also examined trophic interactions between springtails and their potential natural enemies (spiders, ants, and beetles) in both environments. Our results revealed that the abundance and richness of ants and beetles were higher in native forests than in eucalyptus plantations, whereas springtails exhibited a negative response to eucalyptus plantation in terms of abundance, and spiders showed higher richness in eucalyptus plantations. Furthermore, the composition of soil invertebrate communities, with the exception of springtails, was significantly different between eucalyptus plantations and native forests.The correlations between the abundance of springtails and their potential predators (spiders and beetles) were significantly reduced in eucalyptus plantations compared with native forests. Our findings highlight the negative impact of eucalyptus plantation on soil invertebrate diversity and community composition, potentially disrupting predator-prey relationships and emphasizing the importance of preserving native forests to safeguard invertebrate biodiversity and ecological processes.
Keywords: Biodiversity; Brazil; Multi-taxon approach; Silviculture; Trophic groups